Gender-Based Analysis of the Psychological Impact of the COVID-19 Pandemic on Healthcare Workers in Spain - López-Atanes, Mayte; Pijoán-Zubizarreta, José Ignacio; González-Briceño, Juan Pablo; Leonés-Gil, Elena María; Recio-Barbero, María; González-Pinto, Ana; Segarra, Rafael; Sáenz-Herrero, Margarita (Frontiers in Psychiatry, 2021)
Purpose: This study aims to analyze from a gender perspective the psychological distress experienced by the medical workforce during the peak of the pandemic in Spain. Methods: This is a single-center, observational analytic study. The study population comprised all associated health workers of the Cruces University Hospital, invited by email to participate in the survey. It consisted of a form covering demographic data, the general health questionnaire-28 (GHQ-28), and the perceived stress scale (PSS-14). We used multivariant regression analysis to check the effect of gender on the scores. We used gender analysis in both design and interpretation of data following SAGER guidelines. Results: Females made 74,6% of our sample, but their proportion was higher in lower-paid positions such as nursery (89,9%) than in higher-paid ones. The percentage of women categorized as cases with the GHQ-28 was 78,4%, a proportion significantly higher than in the male population (61,3%, p<0,001). The multivariant regression analysis showed that being women, working as orderly staff, and having a past psychiatric history were risk factors for higher scores in both the GHQ-28 and PSS-14. Conclusion: Women and those with lower-paid positions were at risk of higher psychological distress and worse quality of life within the medical workforce during the first wave of the pandemic. Gender analysis must be incorporated to analyze this fact better.